EU-LIFE charter of independent life science research institutes - Superti-Furga, Giulio; Agostinho, Marta; Bury, Jo; Cook, Simon; Durinx, Christine; Ender, Anita; van Luenen, Henri; Lund, Anders H; Medema, René H; Miączyńska, Marta; Nickel, Dorthe; Pelicci, Pier Giuseppe; et al. (FEBS letters, 2024)
The diverse range of organizations contributing to the global research ecosystem is believed to enhance the overall quality and resilience of its output. Mid-sized autonomous research institutes, distinct from universities, play a crucial role in this landscape. They often lead the way in new research fields and experimental methods, including those in social and organizational domains, which are vital for driving innovation. The EU-LIFE alliance was established with the goal of fostering excellence by developing and disseminating best practices among European biomedical research institutes. As directors of the 15 EU-LIFE institutes, we have spent a decade comparing and refining our processes. Now, we are eager to share the insights we've gained. To this end, we have crafted this Charter, outlining 10 principles we deem essential for research institutes to flourish and achieve ground-breaking discoveries. These principles, detailed in the Charter, encompass excellence, independence, training, internationality and inclusivity, mission focus, technological advancement, administrative innovation, cooperation, societal impact, and public engagement. Our aim is to inspire the establishment of new institutes that adhere to these principles and to raise awareness about their significance. We are convinced that they should be viewed a crucial component of any national and international innovation strategies.
Keywords: Academies and Institutes; biologické vědy; Biomedical Research; Biological Science Disciplines; biomedicínský výzkum; akademie a ústavy